(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Exercise and sports are of great importance in strengthening the health of young people in our country, increasing the level of physical fitness and maturing their ability to work. Exercise and sports are considered the main tools in the comprehensive physical development of people.